Pengaruh Stimulasi Janin dan Inisiasi Menyusui Dini terhadap Bonding Attachment - Arista Apriani; Dheny Rohmatika; Yunia Renny Andhikatias; Megayana Yessy Maretta; Wijayanti Wijayanti (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2024)
Fetal stimulation and early initiation of breastfeeding (IMD) have great benefits for the baby's development. This study aims to examine the effect of fetal stimulation and IMD on attachment bonding. This research used a quasi-experimental design, posttest only control design. The experimental group consisted of carrying out fetal stimulation by pregnant women and IMD, while the control group consisted of IMD. Post test to measure bonding attachment. Research location at PMB Wiwik Sumarni, Wonogiri, Central Java in November 2022 – April 2023. Purposive sampling technique with 15 per group. Respondents: Pregnant women with gestational age > 24 weeks were normal and were observed until the IMD process. The result of the independent t-test is significant with a p value of 0.002 (<0.05), the experimental group's posttest score have a lower mean value of 21.60 compared to the control group of 32.67, both groups are in the strong attachment bonding category. ANACOVA results of fetal stimulation and IMD have an attachment bonding score 7 points lower than the control group (b = -7; 95% CI; -13 to -1; p < 0.001). Adjusted R2 = 48.1%. In conclusion, there is an influence of fetal stimulation and IMD on bonding attachment.